Effects Of Modality And Redundancy Principles On The Learning Of Music Theory And Attitude Among Primary Pupils Of Different Aptitudes In Jordan - Aldalalah, Osamah (Mohammad Ameen) Ahmad (2010)

(untitled)
The purpose of this study was to investigate the effects of modality and redundancy principles on the attitude and learning of music theory among primary pupils of different aptitudes in Jordan. The lesson of music theory was developed in three different modes, audio and image (AI), text with image (TI) and audio with image and text (AIT). A 3×3×2 quasi experimental factorial design was adopted in this research. The independent variables were the three modes of courseware. The moderator variables were music intelligence, locus of control and trait anxiety. The dependent variables were the post test score and attitude. The study sample consisted of 405 third-grade pupils and were randomly (simple random sample) selected from six different primary co-education schools. Descriptive and inferential statistics were conducted to analyze the collected data. ANOVA was used to determine the significant differences of the pretest scores among the three groups. Analyses of covariance (ANCOVA) and Post hoc were carried out to examine the main effects as well as the interaction effects of the independent variables on the dependent variables. Simple and Multiple Regression Analysis were used to determine the relative contribution of each factor to the changes in the dependent variable. Seven main hypotheses with six sub- hypotheses were postulated and tested.